1993
DOI: 10.1149/1.2220794
|View full text |Cite
|
Sign up to set email alerts
|

On the Pitting Resistance of Sputter‐Deposited Aluminum Alloys

Abstract: The pitting behavior of sputter-deposited Al binary alloy thin films was studied. Pitting and repassivation potentials were determined in 0.1M NaCl for samples in freshly deposited and air-aged states. Aging for several years in laboratory air increased the pitting potential for some of the alloy systems but had no effect on others. The repassivation potentials, meaningful values for pits in thin films, were found to be very close to the pitting potentials of freshly-deposited films for many alloy systems. Sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
91
0

Year Published

1995
1995
2017
2017

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 124 publications
(98 citation statements)
references
References 12 publications
7
91
0
Order By: Relevance
“…When these tunnels are viewed or stop propagating then they appear bounded by (100) walls. This explanation supports the idea that dissolution of the substrate material dominates the pitting process rather than the nature of the oxide ®lms [23].…”
Section: Discussionsupporting
confidence: 82%
“…When these tunnels are viewed or stop propagating then they appear bounded by (100) walls. This explanation supports the idea that dissolution of the substrate material dominates the pitting process rather than the nature of the oxide ®lms [23].…”
Section: Discussionsupporting
confidence: 82%
“…The determination of thin film pit growth kinetics through the analysis of images of growing pits has indicated that a large portion of the higher pitting potential of these sputtered nonequilibrium Al alloys can be attributed to the ennoblement of the dissolution reaction. 18 To test whether the pit dissolution kinetics were affected by the base pressure, thin film pit growth experiments were performed in this study. As described in the experimental section, a sample surface was observed and recorded while the potential was controlled manually.…”
Section: Resultsmentioning
confidence: 99%
“…18,19 The thin film sample surface was viewed and recorded continuously using a video system. The sample was illuminated from above, which provided strong contrast between the black pitted region and the reflective unpitted region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The overpotential deposition results in stable non-equilibrium alloy phase with uniform composition and structure. Furthermore, the non-equilibrium alloys exhibit similar chloride-induced pitting potentials as those prepared by physical non-equilibrium alloying methods such as rapid solidification, [16][17][18][19] sputter deposition, [20][21][22][23][24][25][26] and ion implantation. 27 Therefore, the electroplating of aluminum alloys from the Lewis acidic chloroaluminate IL is a possible low-cost alternative to conventional non-equilibrium methods for producing thin films of aluminum alloys.…”
mentioning
confidence: 99%